Assessment of Coagulase‐Negative Staphylococci and Lactic Acid Bacteria Isolated from Portuguese Dry Fermented Sausages as Potential Starters Based on Their Biogenic Amine Profile. Issue 10 (5th September 2018) - Alfaia, Cristina M.; Gouveia, Irani M.; Fernandes, Maria H.; Fernandes, Maria J.; Semedo‐Lemsaddek, Teresa; Barreto, António S.; Fraqueza, Maria J.
Abstract : Abstract: The aim of this study was to evaluate the decarboxylase activity of coagulase‐negative staphylococci (CNS) and lactic acid bacteria (LAB) involved in meat products fermentation, in order to characterize and select the strains most suitable to be used as safe starter cultures. Isolates were obtained from traditional Portuguese dry fermented meat sausages, identified by PCR and characterized according to their technological properties. Lactobacilli and enterococci were assessed for their bacteriocinogenic potential. Biogenic amines (BA) were screened by culture method and analyzed by RP‐HPLC/UV. The screening method, compared with chromatographic analysis, was not reliable for CNS and LAB strains selection. Tyramine decarboxylase activity was present in CNS strains, with a slight production of amines. No other hazardous BA were produced. Among lactobacilli, moderate production of tyramine was related only to Lactobacillus curvatus, with some strains producing putrescine or 2‐phenylethylamine. Enterococci were high and moderate producers of tyramine and 2‐phenylethylamine, respectively. Staphylococcus xylosus, Staphylococcus equorum, and Staphylococcus carnosus, independent of their genetic and technological profiles and BA production, were adequate for use in meat products, according to the data. Lactobacillus plantarum and Lactobacillus sakei strains could also be selected for starters. Practical Application: The selection of coagulase‐negative staphylococci and lactic acid bacteria (LAB) isolates were based on their production of biogenic amines in order to avoid this potential hazard production in meat products. The most suitable isolates could be used as safe starter cultures in meat products industry. The staphylococci and LAB selected will achieve particular organoleptic characteristics in meat products and bioprotection from pathogens.